Markt und intellektuelles Kräftefeld. Literaturkritik im Feuilleton von Pariser Tageblatt und Pariser Tageszeitung (1933-1940) - Enderle-Ristori, Michaela (Studien und Texte zur Sozialgeschichte der Literatur, 1997)
The "Pariser Tageblatt", later to become the "Pariser Tageszeitung" (1933-1940), occupies a very special place in the history of the European press in that it was the only daily newspaper by and for German exiles. With reference to the Feuilleton section of this paper the study draws upon archive material to examine the very varied ways in which editorial, economic and aesthetic priorities and constraints can affect and influence the practice of literary reviewing. The approach combines perspectives relating to the history of communicative forms, the sociology of literature and literary criticism. The study is thus in a position to develop a multiple angle on literary reviewing a) as a journalistic institution in the cultural force field of German emigration in France, b) as an economic factor on the literature market, and c) as aesthetic discourse for and with a literary public. This multiple viewpoint gives the study pilot status in the field of the analysis of literary communication in the exile context.